O focus imaginarius : engano e conhecimento na crítica da razão pura - Girotti, Marcio Tadeu (Universidade Federal de São Carlos, 2016)
Starting from Kant’s statement that there is an inherent transcendental illusion in the process of knowledge, we ask: how can an illusion have a positive role? It is possible to identify a paradox, that can be, considering Kant’s statement itself, overcome by a critique of reason and by a careful reading to the positive role of the transcendental idea to the empirical knowledge. By criticizing traditional metaphysics, in the same time that he shows how illusion can stop deceiving, even imperative, Kant guarantees a role to reason on knowledge sphere, engendering the way to nature’s unity desired by reason. Kant (KrV, B 673) states that focus imaginarius is an inseparable aspect of the transcendental idea and of its empirical knowledge regulator role. Considering the existence of a transcendental idea as a figurative unity projected as focus imaginarius, our goal is to show that the reason paradox can be overcome form focus imaginarius critical metaphor, as an entity of being, featured by Kant as an analogy to the transcendental idea, that takes part of knowledge game as reason’s deprecated unity, bringing forward the very reasons objects. As this investigations exemplary moment, is seen, through reason’s antinomies example, that reasons demands a systematic unity of all knowledge, by having the transcendental idea as this unity, featured from a projection: the focus imaginarius.
Keywords: Ilusão transcendental; Paradoxo; Razão; Conhecimento; Focus imaginarius; Transcendental illusion; Paradox; Reason; Knowledge; Focus imaginarius; CIENCIAS HUMANAS::FILOSOFIA